Multi-Spectral Metasurface With High Optical Transparency, Low Infrared Surface Emissivity, and Wideband Microwave Absorption - Huang, Sining; Fan, Qi; Wang, Jiafu; Xu, Cuilian; Wang, Binke; Yang, Baiyu; Tian, Changhui; Meng, Zhen (Frontiers in Physics, 2020)
In this paper, we propose the design of a multi-spectral metasurface(MSM) which can simultaneously achieve quite good optical transparency, low infrared emissivity and wideband microwave absorption. To this end, optically transparent materials were used in the MSM design, including indium tin oxide, Polyethylene terephthalate and polymethyl methacrylate. The MSM is composed of three functional layers: a frequency selective surface (FSS) on the top, a resistively absorbing layer in the middle and a complete conducting sheet at the bottom. Due to large occupation ratio (OR) of conducting area and the low-pass property of the FSS, electromagnetic waves are allowed to penetrate through it into the middle absorbing layer, simultaneously with low surface infrared emissivity. A prototype was designed, fabricated and measured. Both the simulation and experiment results show that the MSM can achieve strong absorption over 90% in 12.03- 29.43GHz and low IR emissivity about 0.3 in 3.0-14.0μm simultaneously. Moreover, the average optical transparency is higher than 90%. Due to the excellent multispectral compatibility, the MSM may find applications in electromagnetic protection, stealth technologies, etc.